Analisis Tingkat Erosi dan Perencanaan Konservasi Berbasis Sistem Informasi Geografis di Kecamatan Rendang, Kabupaten Karangasem, Provinsi Bali - THRESIA ADHISYA SITORUS; MADE SRI SUMARNIASIH; NI MADE TRIGUNASIH (Fakultas Pertanian Universitas Udayana, 2023)
Erosion Level Analysis and Conservation Planning Based on Geographic Information Systems in Rendang District, Karangasem Regency, Bali Province. The factor of rapid population growth leads to land conversion and slopes used as agricultural land. In Rendang District erosion can be caused by unaccordance land use with conservation principles and Regosol soil types. This study aims to determine the level of erosion and its distribution, the amount of erosion allowed and appropriate conservation planning in Rendang District. The methods used are surveys and Universal Soil Loss Equation (USLE). The result of this study are Rendang District has erosion levels from very light to very heavy, with values ranging from 0.35-809 tons/ha/year. Land unit 1, 2, 10, and 16 have very light levels with total area of 4,302.43 ha. Light levels are found in land unit 9, 13 and 17 with total area of 429.23 ha. Moderate levels are found in land unit 3, 12, 14, 15 and 18 with total area of 1,369.83 ha. Heavy levels are found in land unit 6, 7 and 11 with total area of 1,829.91 ha. Very heavy levels are found in land unit 4, 5 and 8 with total area of 1,529.32 ha. The allowed erosion value in Rendang District is 11-36.10 tons/ha/year. The recommended conservation planning is the improvement of vegetation factors and land management if the erosion is higher than the allowed erosion, otherwise it needs to be preserved.